Conformity and psychological well-being among early adults without romantic relationship experience - Mutiara Mona; Deitje Katuuk; Gloridei Lingkanbene Kapahang; Yeheskiel Entaren (JOURNAL OF Mental Health Concerns, 2026)
Background: Early adulthood is often characterized by various social demands, including expectations related to romantic relationships. Individuals who have never dated frequently experience social pressure from their peer environment, which may potentially affect their psychological well-being. Purpose: To examine the effect of conformity on psychological well-being among early adults who have never been in a romantic relationship. Method: A quantitative causal (explanatory) research design to examine the effect of conformity on psychological well-being among early adults who had never been involved in a romantic relationship. The research participants consisted of 98 active students at Universitas Negeri Manado who had never been in a romantic relationship, selected through purposive sampling. The research instruments included a conformity scale and a psychological well-being scale. Data were analyzed using simple linear regression with a bootstrapping technique. Results: A significant negative effect of conformity on psychological well-being (p = 0.000; R² = 0.291). This finding suggests that higher levels of conformity are associated with lower levels of psychological well-being. Conformity accounted for 29.1% of the variance in psychological well-being, while the remaining 70.9% was influenced by other factors not examined in this study. Additional analyses showed that the effect of conformity was stronger among male respondents (34.3%) compared to female respondents (24.9%).These findings indicate that social pressure encouraging excessive conformity can reduce the psychological well-being of early adults who have never been in a romantic relationship. Conclusion: This study is expected to serve as a reference for psychology practitioners and counselors in developing intervention services that focus on strengthening autonomy, self-confidence, and coping skills in dealing with social pressure. Keywords: Conformity; Early Adulthood; Never Been In A Romantic Relationship; Psychological Well-Being.